Occupational Future Time Perspective: Psychometric Properties of a Spanish Scale - Topa, Gabriela; Zacher, Hannes (Frontiers in Psychology, 2018)
Occupational future time perspective (OFTP) describes people’s perceptions of their future in the work context. In this study, we examined the psychometric properties of a Spanish OFTP scale (OFTP-SP). Data came from two samples of workers in Spain aged between 21 and 62 years (Study 1; N = 496) and between 40 and 70 years (Study 2; N = 386). In Study 1, we conducted descriptive analyses for the items and exploratory factor analysis. In Study 2, we conducted confirmatory factor analyses (CFA). Predictive validity of the OFTP-SP was examined based on relationships with employees’ motivation to continue working and retirement intentions. Results showed that reliability estimates were adequate, and hypotheses regarding the concurrent predictive validity for the three factors of the OFTP-SP (i.e., perceived remaining time, focus on opportunities, focus on limitations) were supported. The OFTP-SP is a psychometrically sound measure that can be used in future research on work and aging.